2021
DOI: 10.1021/acsami.0c21889
|View full text |Cite
|
Sign up to set email alerts
|

A Diradicaloid Small Molecular Nanotheranostic with Strong Near-Infrared Absorbance for Effective Cancer Photoacoustic Imaging and Photothermal Therapy

Abstract: Organic small molecule-based phototheranostics hold great promise for clinical translation by virtue of their distinct chemical structure, easy reproducibility, and high purity. However, reported molecular agents typically have relatively low optical absorbances, particularly over the near-infrared (NIR) region, and this limits their phototheranostic performance. Herein, we first exploit a diradicaloid molecular structure for enhancing NIR absorption to facilitate efficient photoacoustic imaging (PAI)-guided p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Reproduced with permission. [45] Copyright 2021, American Chemical Society from 16.3% to 31.6%. Compared with traditional radical synthesis method via covalent chemistry, the method they established via supramolecular chemistry is much simpler.…”
Section:  Photothermal Therapy (Ptt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [45] Copyright 2021, American Chemical Society from 16.3% to 31.6%. Compared with traditional radical synthesis method via covalent chemistry, the method they established via supramolecular chemistry is much simpler.…”
Section:  Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…Lee et al also exploit a novel carbon-centered diradical DRM, which is composed of a strong donor (N,N-bis(4-butoxyphenyl)thiophen-2-amine) and a robust acceptor (croconic acid), as shown in Figure 8E. [45] Obvious feature of radical was observed in EPR spectra of the DRM because of efficient charge transfer via interaction between donor and acceptor (Figure 8F). After assembling DRM into nanoparticles (Figure 8E), DRM NPs show desirable absorption at∼790 nm, which is highly favorable for NIR PTT.…”
Section: Carbon-centered Diradicalmentioning
confidence: 99%
“…Currently, more recent studies have shown superior performance of CPs in the PA imaging field and successfully applied for real-time photoactivable theranostics. [130][131][132][133][134] [104] Copyright 2017, Nature Publishing Group.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…[37,39,40] Taking advantage of their tunable molecular structures, light-harvesting windows of semiconducting small molecules can easily covered the entire visible and the NIR regions, thus holding great promise for various biomedical applications. [38,[41][42][43][44][45][46][47][48][49][50][51] Notably, recent advances in semiconducting small molecules-based non-radiative transitions have been made for efficient photothermal therapy (PTT) and photoacoustic imaging (PAI) in vivo, especially in the NIR-I and the NIR-II windows. In respect of fluorescence properties, semiconducting small molecules can effectively coordinate the conjugated units to achieve high brightness fluorescence in the visible and the NIR ranges.…”
Section: Introductionmentioning
confidence: 99%